Information sources as predictors of knowledge of exclusive breastfeeding among nursing mothers in Anambra South Eastern Nigeria (2019)
Exclusive Breastfeeding (EBF) practice has become global phenomenon considered gold standard for optimal infant health care. Variations in proportions of women adopting appropriate breastfeeding practices have been observed and these are important from a medical perspective, as individual's decisions on breastfeeding have implications for infant health. Aware that poor knowledge of EBF has been linked to its non-adoption, this study investigated influence of information sources on knowledge of EBF among nursing mothers in Anambra State, South-Eastern Nigeria. Information Processing Theory provided the theoretical underpin while survey and Focus Group Discussion (FGD) were employed as research designs. Two hundred and eleven systematically selected nursing mothers responded to the questionnaire while 24 purposively selected discussants took part in the FGD. Finding revealed that health personnel (HP) especially nurses were major information sources on EBF practices. Pearson's correlation analysis showed a significant relationship between mass media (specifically radio, billboards/posters) and nursing mothers' knowledge of EBF. Stakeholders in health sector, including Federal and State governments, non-governmental organizations (NGOs), donor agencies and other health planners involved in health campaign, are advised to adopt radio as a channel of communication especially in rural communities where knowledge of EBF needs to be scaled up.